Bioethics Beyond Altruism : Donating and Transforming Human Biological Materials - Shaw, Rhonda M. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book departs from conventional bioethics approaches to consider the different moral and political economies involved in the donation and transformation of human organs, gametes, stem cells and breastmilk. Collectively, the authors draw attention to the different values associated with research and therapy on body part and tissue exchange through an examination of altruism, gift and commodity relations. They expertly discuss issues such as the bioethical conundrums around the circulation and use of human biological materials and services as well as their legal and regulatory limits, the economic benefits and health values attributed to various body parts and products, and the matter of immaterial labour and affective relations between donors, recipients and others involved in tissue provision. Based on new empirical research, this interdisciplinary collection of original and timely essays will be of interest to students and researchers in gender and cultural studies, sociology, anthropology, science and technology studies, as well as medical professionals with an interest in health and reproduction.
Keywords: Social sciences.; Bioethics.; Medical ethics.; Social medicine.; Human body -- Social aspects.; elektronické knihy; electronic books